Satiety-enhancing placebo intervention decreases selective attention to food cues - Marina Lanz; Marina Lanz; Verena Hoffmann; Karin Meissner; Karin Meissner (Frontiers in Psychiatry)
BackgroundAs placebo interventions could influence appetite and satiety in first studies, they are a promising tool for the future treatment of obesity. Furthermore, individuals with heightened body weight show increased selective attention for food cues. This study aimed to investigate whether placebo induced changes of appetite and satiety can affect attention allocation and to examine correlating factors.MethodsIn a double-blind design, 63 healthy participants were randomized into one of three groups: the enhanced appetite placebo group, the enhanced satiety placebo group, or the control group. Appetite and satiety were induced by administering a placebo capsule along with a group specific expectancy manipulation. One hour later, participants performed a visual probe task to measure attentional bias by comparing reaction times for different conditions. Correlations between reaction times and subjective hunger and satiety ratings, as well as current food craving and plasma ghrelin levels, were explored.ResultsThe induction of attentional bias toward non-food stimuli was successful in women in the enhanced satiety placebo group but not in the enhanced appetite placebo group. Women of the enhanced satiety placebo group showed significantly higher reaction times for food cues compared to non-food cues. Across conditions, reaction times were associated with subjective hunger ratings and current food craving in women. No attentional bias was induced in men in either placebo group.ConclusionPlacebo-induced satiety inhibited attention allocation toward food in healthy women, potentially mediated by reduced hunger and food craving. Placebo effects on satiety could thus be demonstrated on a highly complex cognitive process.